A phylogeny for African Pipistrellus species with the description of a new species from West Africa (Mammalia: Chiroptera). Issue 2 (4th September 2020) - Monadjem, Ara; Richards, Leigh R; Decher, Jan; Hutterer, Rainer; Mamba, Mnqobi L; Guyton, Jen; Naskrecki, Piotr; Markotter, Wanda; Wipfler, Benjamin; Kropff, Anna S; Dalton, Desire L
Abstract: Pipistrelloid bats are among the most poorly known bats in Africa, a status no doubt exacerbated by their small size, drab brown fur and general similarity in external morphology. The systematic relationships of these bats have been a matter of debate for decades, and despite some recent molecular studies, much confusion remains. Adding to the confusion has been the recent discovery of numerous new species. Using two mitochondrial genes, we present a phylogeny for this group that supports the existence of three main clades in Africa: Pipistrellus, Neoromicia and the recently described Parahypsugo . However, the basal branches of the tree are poorly supported. Using an integrative taxonomic approach, we describe a new species of Pipistrellus sp. nov. from West Africa, which has been cited as Pipistrellus cf. grandidieri in the literature. We demonstrate that it is not closely related to Pipistrellus grandidieri from East Africa, but instead is sister to Pipistrellus hesperidus . Furthermore, the species Pi. grandidieri appears to be embedded in the newly described genus Parahypsugo, and is therefore better placed in that genus than in Pipistrellus . This has important taxonomic implications, because a new subgenus ( Afropipistrellus ) described for Pi. grandidieri predates Parahypsugo and should therefore be used for the entire " Parahypsugo " clade. The Upper Guinea rainforest zone, and particularly the upland areas in the south-eastern Guinea—northern Liberia border region may represent a global hotspot for pipistrelloid bats and should receive increased conservation focus as a result.